Role of the Ubiquitin C-Terminal Hydrolase L1-Modulated Ubiquitin Proteasome System in Auditory Cortex Senescence - Zhang, Ya; Huang, Xiang; Zhao, Xue-Yan; Hu, Yu-Juan; Sun, Hai-Ying; Kong, Wei-Jia (O.R.L. Journal for oto-rhino-laryngology and its related specialties, 2017)
According to recent studies, central auditory impairments are closely related to neurodegenerative diseases. However, the mechanism of central presbycusis remains unclear. Ubiquitin C-terminal hydrolase L1 (UCHL1) is important in maintaining proteasomal activity; however, the detailed mechanism has not yet been fully elucidated. This study aims to investigate the molecular alterations involved in UCHL1 regulation during auditory cortex aging. D-Galactose (D-gal) induces oxidative stress and senescence in the auditory cortex, as reported in our previous studies. Primary auditory cortex cells were treated with D-gal for 72 h or 5 days. The proteins related to the ubiquitin proteasome system (UPS) and proteasomal activities were evaluated. UCHL1 was overexpressed, and the effects of UCHL1 on the UPS and proteasomal activity were analyzed. Proteasomal activity was elevated at 72 h and decreased at 5 days in D-gal-treated primary auditory cortex cells. We also found that overexpression of UCHL1 increased the UPS-related proteins UBE1, PSMA7, ubiquitinated proteins, and monoubiquitin, and proteasomal activity. The results suggest that UCHL1 may modify the aging process in the auditory cortex by regulating UPS- related proteins.